2022
DOI: 10.1097/ijg.0000000000001998
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes of the Paul Glaucoma Implant for Treatment of Glaucoma

Abstract: Purpose: To determine 2-year efficacy of the PAUL Glaucoma Implant (PGI), a novel glaucoma tube shunt in patients with advanced glaucoma. Participants: Patients with glaucoma refractory to maximum medical therapy or previous failed glaucoma surgery. Methods: Retrospective review of all patients who had underwent PGI implantation in a single tertiary institution between May 1, 2017 and March 30, 2021. Main Outcome Measures: Primary outcome measure was failure defined as intraocular pressure (IOP) >18 mm H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
4
9
1
1
Order By: Relevance
“…15 Tan et al reported ocular hypotony in 10 out of 45 eyes with four needing an additional intervention due to its persistence. 16 Study results from Vallabh et al and José et al are in concordance to our findings and underscore the low complication rate of the PGI, especially with regard to postoperative hypotony. In comparison to Tan et al, we found a lower postoperative hypotony rate.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…15 Tan et al reported ocular hypotony in 10 out of 45 eyes with four needing an additional intervention due to its persistence. 16 Study results from Vallabh et al and José et al are in concordance to our findings and underscore the low complication rate of the PGI, especially with regard to postoperative hypotony. In comparison to Tan et al, we found a lower postoperative hypotony rate.…”
Section: Resultssupporting
confidence: 92%
“…Their results are comparable to our data albeit their study including two-year results. 16 Our results confirm that the PGI leads to a significant reduction of IOP and considerably lowers the number of antiglaucomatous eye drops at a low complication rate.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Ambos implantes permiten un control efectivo de la PIO en nuestro seguimiento a tres meses. En la literatura se describe un porcentaje de éxito del 93.2% a un año de seguimiento con PGI y una PIO promedio a los tres meses de 14.54 mmHg, lo cual concuerda con nuestros resultados de 13.8 mmHg 9,10 . En nuestros casos no hubo diferencias en el número de gotas hipotensoras postoperatorias entre ambos grupos, ni tampoco al comparar las gotas preoperatorias y postoperatorias.…”
Section: Discussionunclassified
“…Postoperative complications such as the presence of a shallow anterior chamber was seen in 22% of patients but most of these was self-limiting, hypotony requiring further intervention was seen in 9% of patients and tube occlusion was also seen in 9% of patients. However, literature evaluating its efficacy in uveitic glaucoma eyes is limited at present [30 ▪ ].…”
Section: Conventional Surgical Optionsmentioning
confidence: 99%